2016
DOI: 10.1002/ajmg.b.32462
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐gene sequencing investigation ofSAT1in attempted suicide

Abstract: Suicidal behavior imposes a tremendous cost, with current US estimates reporting approximately 1.3 million suicide attempts and more than 40,000 suicide deaths each year. Several recent research efforts have identified an association between suicidal behavior and the expression level of the spermidine/spermine N1-acetyltransferase 1 (SAT1) gene. To date, several SAT1 genetic variants have been inconsistently associated with altered gene expression and/or directly with suicidal behavior. To clarify the role SAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…An example is a shared region in family 601627 with genome-wide significance (p=1.94E-10). A single gene in this region, neurexin 1 ( NRXN1 ), has evidence from the published literature of involvement in psychiatric risk [48] and inconclusive evidence for risk of suicide [54]. The shared region in family 601627 is shared by six cases, shown in Figure S4 in the supplemental material.…”
Section: Case Studiesmentioning
confidence: 99%
“…An example is a shared region in family 601627 with genome-wide significance (p=1.94E-10). A single gene in this region, neurexin 1 ( NRXN1 ), has evidence from the published literature of involvement in psychiatric risk [48] and inconclusive evidence for risk of suicide [54]. The shared region in family 601627 is shared by six cases, shown in Figure S4 in the supplemental material.…”
Section: Case Studiesmentioning
confidence: 99%
“…These studies have identified additional targets that may contribute to the risk of suicidal behavior, but very few implicated sites have been replicated [25,26]. Further, few implicated candidate genes have been deeply assessed for the possibility that rare functional variation within them might contribute to the phenotype [27,28,29]. …”
Section: Introductionmentioning
confidence: 99%
“…Chapter 4 discusses an effort to completely sequence the candidate gene, SAT1, along with surrounding regulatory features near the gene locus. The complete project and our findings are described in the form of the published manuscript, "Whole-gene sequencing investigation of SAT1 in attempted suicide" (41). We selected the SAT1 gene due to extensive focus this gene has recently received within the literature.…”
Section: Suicidal Behavior Targeted Sequencing Projectmentioning
confidence: 99%
“…Further, few implicated candidate genes have been deeply assessed for the possibility that rare functional variation within them might contribute to the phenotype (36,37,41).…”
Section: Chapter 3 Complete Published Manuscript "Assessment Of Whomentioning
confidence: 99%
See 1 more Smart Citation